Effect of Internal Curing with Superabsorbent Polymers on Bond Behavior of High-Strength Concrete - Xiao Lei; Rui Wang; Hanwan Jiang; Faxiang Xie; Yanni Bao (Advances in Materials Science and Engineering)
High-strength concrete (HSC) is widely used in engineering due to its high strength and durability. However, because of its low water-to-cement ratio, external curing water hardly enters the dense internal structure of HSC so that high self-desiccation shrinkage often takes place. As a result, superabsorbent polymers (SAP) are added as an internal curing material to effectively reduce the shrinkage of high-performance concrete. Meanwhile, the bond performance between reinforcing steel and SAP HSC concrete remains unknown. In this paper, the bond performance of HSC mixed with SAP is studied by pull-out tests, and the results were obtained as follows: (1) the bond strength of HSC mixed with SAP increased first and then decreased with the increase of SAP content; (2) the slip at ultimate bond strength of HSC with SAP decreased with the increase of compressive strength; (3) a prediction model of the stress-slip relationship between steel rebars and HSC was established.